Impacts of climatic changes on building maintenance in mosque at Seri Iskandar / Nur Fatin Natasha Mazlan and Norehan Mohd. Noor - Mazlan, Nur Fatin Natasha; Mohd. Noor, Norehan (2023)
This study investigates the repercussions of climate change on building maintenance, focusing on two mosques in Bandar Baru Seri Iskandar, Perak, Malaysia. With weather reports indicating an annual temperature rise of approximately 0.24°C since 1961 and changes in rainfall patterns, extreme climate events such as heavy rains, storms, and heatwaves have become more frequent. These climate-induced phenomena have resulted in damages to building elements, particularly roofs and main structures, leading to consistent and repeated maintenance requirements. Roof leaks and mold/mildew growth were found to be the most common issues caused by extreme weather conditions. The study emphasizes the necessity of incorporating climate factors into building maintenance planning and advocating for dedicated financial allocations to address the increasing challenges posed by climate change. By proactively adapting maintenance practices, buildings can better withstand the impacts of climate change and safeguard infrastructure in the face of an evolving climate.